Decoding the artefactual memory. Strengths of the integral analysis of lithic artefacts - Babot, María del Pilar; Hocsman, Salomón (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
This work addresses the so-called integral analysis approach of lithic artefacts. This is an interdisciplinary methodological approach that articulates different analytical strategies of the artefact imprinted memory, variable depending on the case, for a comprehensive and thorough understanding of the life history of flaked artefacts, ground stone tools, and objects modified by use. The lines of evidence and analytical lines that are combined in this perspective are diverse and situational, namely, detailed techno-typological analysis; residue analysis; use wear analysis; taphonomic and contextual studies; among others. The proposal is based on the consideration of these multiple lines as complementary, that is, lacking a hierarchical relationship, which interpellate and dialogue with each other, in a non-destructive or low-impact microdestructive approach, where contextual information is relevant. In this regard, a series of concepts, experiences and knowledge from several collaborations aimed at the comprehensive study of lithic artifacts, are exposed, corresponding to hunter-gatherers and agro-pastoral societies in Southern South America.